Information aggregation with costly reporting - Obsborne, M.J., Rosenthal, J.S. and Stewart, C. (The Economic Journal: A Journal of the Royal Economic Society)
A group of privately informed individuals with common interests chooses a binary option. Each individual chooses whether to reveal her signal, at a cost. If the group is large and cannot commit to a decision rule then it takes the correct decision with high probability in one state but with probability bounded away from one in the other. It cannot do better by committing to an anonymous decision rule without transfers, but can achieve the first best if transfers between individuals are possible, and can approximately achieve the first best with a non-anonymous decision rule.- Reproduced